Penguatan Kapasitas Kader Posyandu dalam Pengembangan MP-ASI Pangan Lokal sebagai Upaya Antisipasi Stunting: Pengabdian - Akmal Izwar; Elfiana Elfiana; Naya Desparita; Syahirman Hakim; Muliani Muliani; Anis Nugrahawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Stunting remains a major public health issue in Aceh Province, including Bireuen Regency, which records a prevalence of 26.5%. One of the main contributing factors is the improper provision of complementary feeding (MP-ASI), particularly regarding nutritional composition and the limited use of local food ingredients. This community service program aimed to enhance the capacity of Posyandu cadres in Pante Karya Village to develop locally sourced complementary foods as a strategy to prevent stunting. The methods included education sessions, hands-on MP-ASI preparation training, and post-training mentoring through field visits. The results showed an increase in cadres’ knowledge and skills in designing nutritionally balanced MP-ASI menus, with an average knowledge improvement of 35%. Participants successfully utilized local food ingredients such as fish, tempeh, and vegetables as sources of protein and micronutrients. This program demonstrates that participatory and practical-based training effectively improves cadre capacity and contributes to sustainable stunting prevention efforts at the community level. Keywords: Posyandu cadres, Complementary Feeding, Local Food, Stunting, Community Service